Construction waste estimating model for residential housing projects in Selangor and Kuala Lumpur / Asmawati Che Hasan - Che Hasan, Asmawati (2013)
Construction waste issues have become a major concern in most countries but in Malaysia, awareness on the documentation of construction waste generated is still lacking although such record may offer a better management system. Various models in quantifying the construction waste materials have been developed in many countries to improve the management of construction waste. Therefore, this thesis intends to provide models to predict the waste’s amount of timber, steel, concrete and bricks generated from a housing project. Variables contributed to the construction waste generation were identified from literature review and were arranged in a structured questionnaire survey. This survey was distributed among Grade seven local contractors in Selangor and Kuala Lumpur area. Besides, archival data comprised of taking off, delivery order and as built drawing of the residential projects within the last three years of duration were collected from contractors in these areas. The findings of the survey resulted that planning of materials was found to be the most significant factor affecting the generation of waste while total cost of the project is opposed. The models developed for timber, concrete, steel and bricks shown the adjusted R-square value of 0.851, 0.535, 0.833 and 0.418 respectively. The performances of the models were evaluated by using the mean absolute percentage error (MAPE) where good model shown value less than 20% (15.478% of timber) and common for range 20%-50% for steel, concrete and brick model with percentage 23.856%, 32.71% and 35.256% respectively. The models developed are believed can assist the practitioners and contractors in estimating the waste will be generated and hence preparing the proper waste management.